Stereoelectroencephalography in the preoperative assessment of patients with refractory focal epilepsy: experience at an epilepsy centre - R. Toledano; R. Martínez-Alvarez; A. Jiménez-Huete; I. García-Morales; Á. Aledo-Serrano; W. Cabrera; G. Rey; P. Campo; J.C. Gómez-Angulo; I. Blumcke; J. Álvarez-Linera; J.M. del Pozo; et al. (Neurología (English Edition), 2022)
Objective: Stereoelectroencephalography (SEEG) is a technique for preoperative evaluation of patients with difficult-to-localise refractory focal epilepsy (DLRFE), enabling the study of deep cortical structures. The procedure, which is increasingly used in international epilepsy centres, has not been fully developed in Spain. We describe our experience with SEEG in the preoperative evaluation of DLRFE. Material and methods: In the last 8 years, 71 patients with DLRFE were evaluated with SEEG in our epilepsy centre. We prospectively analysed our results in terms of localisation of the epileptogenic zone (EZ), surgical outcomes, and complications associated with the procedure. Results: The median age of the sample was 30 years (range, 4-59 years); 27 patients (38%) were women. Forty-five patients (63.4%) showed no abnormalities on brain MR images. A total of 627 electrodes were implanted (median, 9 electrodes per patient; range, 1-17), and 50% of implantations were multilobar. The EZ was identified in 64 patients (90.1%), and was extratemporal or temporal plus in 66% of the cases. Follow-up was over one year in 55 of the 61 patients undergoing surgery: in the last year of follow-up, 58.2% were seizure-free (Engel Epilepsy Surgery Outcome Scale class I) and 76.4% had good outcomes (Engel I-II). Three patients (4.2%) presented brain haemorrhages. Conclusion: SEEG enables localisation of the EZ in patients in whom this was previously impossible, offering better surgical outcomes than other invasive techniques while having a relatively low rate of complications. Resumen: Objetivo: La estereoelectroencefalografía (E-EEG) es una técnica de evaluación prequirúrgica en pacientes con epilepsia focal refractaria de difícil localización (EFRDL) que permite explorar con electrodos profundos regiones cerebrales de difícil acceso y la profundidad de la corteza. Esta técnica, en auge en centros internacionales, apenas se ha desarrollado en España. Describimos nuestra experiencia con la E-EEG en la evaluación de pacientes con EFRDL. Material y métodos: En los últimos 8 años, 71 pacientes con EFRDL fueron evaluados con E-EEG en nuestro centro. Analizamos prospectivamente los resultados obtenidos en la localización, los resultados quirúrgicos y las complicaciones asociadas a la técnica. Resultados: La mediana de edad fue de 30 años (rango 4-59 años), 27 pacientes eran mujeres (38%). La RM cerebral fue negativa en 45 pacientes (63,4%). Se implantaron 627 electrodos (mediana de 9 electrodos por paciente, rango 1-17), con un 50% de implantaciones multilobares. En 64 (90,1%) pacientes se localizó la zona epileptógena (ZE), siendo extratemporal o temporal plus en el 66% de los casos. En 55 pacientes de los 61 intervenidos el seguimiento fue superior al año: en el último año de seguimiento 32/55 pacientes (58,2%) estaban libres de crisis (Engel I) siendo los resultados favorables (Engel I-II) en el 76,4% de las intervenciones. Tres pacientes (4,2%) presentaron una hemorragia cerebral. Conclusión: La E-EEG permite localizar la ZE en pacientes en quienes anteriormente no era posible, ofreciendo unos resultados quirúrgicos superiores a otras técnicas invasivas y una tasa de complicaciones relativamente baja.